Adolescent Sex Differences in Response to a Mindfulness Intervention: A Call for Research - Bluth, Karen (J Child Fam Stud, 2017)
Research on mindfulness interventions with adolescents has burgeoned over the last ten years, and findings have demonstrated increases in overall emotional wellbeing post-intervention. However, little is known about the differences between males and females in response to mindfulness interventions in this age group. In the present study we examine sex differences in outcomes of physiological stress markers during the Trier Social Stress Test (TSST) and emotional wellbeing measures before and after a mindfulness intervention (N = 15) with 10 female and 5 male adolescents. Additionally, we examine sex differences in course engagement and post-intervention use of mindfulness skills during the TSST. Overall, we found some evidence that females were more engaged than males in the class and also reported less stress post-intervention. We conclude by strongly encouraging future research in this area to more clearly elucidate the different ways in which adolescent males and females engage and respond to mindfulness interventions.